Cognitive Load and Test-Taking Skills as Correlates of Academic Performance in Mathematics of Joint Universities Preliminary Examinations Board Science Students, University of Benin - Adeosun, Praise Kehinde; Okonkwo, Nkechinyere Onyinye (NIU Journal of Social Sciences; Vol 10 No 2 (2024): NIU Journal of Social Sciences, Vol. 10 No. 2, June 2024, 2024)
This study was conducted to determine whether cognitive load and test-taking skills are correlates of academic performance in mathematics of Joint Universities Preliminary Examinations Board (JUPEB) Science students, University of Benin, Benin City. The study was hinged on Cognitive Load Theory (CLT) and Cognitive Social Learning Theory (CSLT). CLT was developed by Sweller (1988) while CSLT was developed by Bandura (1977, 1986). To guide this study, three research questions were raised which were also hypothesized and tested at 0.05 significant level. Survey design with correlational approach was adopted for the study. The population of the study consists of 82 JUPEB science students. The sample of the study was also 82 students as the population was small. Data was collected using an adapted instrument which was modified and titled “JUPEB Students’ Cognitive Load and Test-taking Skills Questionnaire (JSCLTSQ)”. The instrument was content-validated. Three experts from the Department of Educational Evaluation and Counselling Psychology made some corrections and suggestions which were incorporated into the final copy and thereafter certified valid for use for the study. The instrument was trial-tested on 20 students and the reliability was determined using the Cronbach Alpha statistics which yielded coefficients of 0.85 and 0.81 for the two subscales respectively. The three (3) hypotheses were tested using the Pearson Product Moment Correction Coefficient statistics. The findings revealed that cognitive load has a low inverse relationship with academic performance in mathematics while test-taking skills has a positive relationship with academic performance in mathematics. Cognitive load and test-taking skills are jointly correlated with academic performance in mathematics. Based on the findings, some recommendations were made. One of such recommendations is that tutors of JUPEB University of Benin need constant attendance in seminars and workshops funded by the government and the school management on various cognitive load issues and effective test-taking strategies. Keywords: Cognitive load, Test Taking Skills, Academic Performance